Semiconductors for Photocatalysis - Mi, Zetian; Wang, Lianzhou (Chemical engineer); Jagadish, C. (Chennupati) (Semiconductors and semimetals, 2017)
Semiconductors for Photocatalysis, Volume 97, covers the latest breakthrough research and exciting developments in semiconductor photocatalysts and electrodes for water splitting and CO2 reduction. It includes a broad range of materials such as metal-oxides, metal-nitrides, silicon, III-V semiconductors, and the emerging layered compounds. The design and modeling of photocatalysts and photoelectrodes and the fundamental mechanisms of water splitting and CO2 reduction is also discussed.